Water-saving strategies in the mining industry – The potential of mineral processing simulators as a tool for their implementation. (15th March 2019) - Michaux, B.; Hannula, J.; Rudolph, M.; Reuter, M.A.; van den Boogaart, K.G.; Möckel, R.; Kobylin, P.; Hultgren, M.; Peltomäki, M.; Roine, A.; Remes, A.
Abstract: As the mining industry is facing an increasing number of issues related to its fresh water consumption, water-saving strategies are progressively being implemented in the mineral processing plants, often leading to variations in the process water chemistry. However, the impact of water chemistry variations on the process performance is rarely known beforehand, thus creating an obstacle to the implementation of those water-saving strategies. To tackle this problem, the effect the different dissolved species present in the process water have on the processing plant performance must be quantified, and this information must be digitalized in a practical and suitable form to be used in mineral processing simulators. To achieve this goal, a methodology to digitalize the influence of the process water composition on the flotation performance is presented in this paper. Using the flotation of a fluorite ore as case study, the relationship between process water composition and the flotation kinetics of that fluorite ore was determined. This relationship was digitalized in HSC Sim, a mineral processing simulator, turning it into a tool capable of simulating the flotation performance under a variety of process water compositions. Finally, the potential of this new tool to help implementing water-saving strategies on the mine site is discussed, and the challenges that need to be overcome in order to apply this tool at industrial scale are being addressed. Graphical abstract: Image 10064 Highlights: Simulation-based approach is introduced to implement water-saving strategies. The simulation platform HSC Sim was developed to account for water chemistry. A methodology was developed to include water chemistry effects in HSC Sim. Water chemistry was optimized through simulation to maximize flotation performance. Challenges to implement water-saving strategies through simulation are addressed.